Research Therapeutics at the King Saud bin Abdulaziz University for Health Sciences: A Bibliometric Assessment - Ikram Ul Haq,Khalid A Fouyza,Pervaiz Ahmed (IJoLIS, 2024)
Purpose: To carry out bibliometric assessment of researchoutput on Therapeuties affiliated with Kingt Saud Bib Abdul aziz University for HeaLTH sCIENCES9ksau-hs), its teaching hospital and research centre.